PENGARUH PUPUK ORGANIK CAIR BATANG PISANG KEPOK TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS TIGA JENIS TANAMAN SAWI - Linna Fitriani; Yuni Krisnawati; Destien Atmi Arisandy (Jurnal Biosilampari : Jurnal Biologi, 2019)
The purpose of this research is to determine the effect of liquid organic fertilizer of banana stem on the growth and productivity of 3 types of mustard. This type of research is a descriptive quantitative with an experimental method. The study design used a completely randomized design (CRD) with three treatments and eight replications. Data collection by observation using observation sheets. The data obtained were analyzed by analysis of variance (ANOVA) in one path and continued with LSD. Based on the results of the research, there are differences in the effect of giving Liquid Organic Fertilizer to banana stem on the plant height parameters of three types of mustard. The plant height parameters of chinese green cabbage, and collards meat are significantly different from those of green mustard. There are differences in the effect of giving Liquid Organic Fertilizer banana stem to the parameters of the number of leaves of three types of mustard. The parameters of the number of chinese green cabbage and green mustard leaves are significantly different from collards meat. There is a difference in the effect of Liquid Organic Fertilizer on banana stem on the wet weight parameters of three types of mustard. The parameters of wet weight of chinese green cabbage and green mustard are significantly different from collards meat. The purpose of this research is to determine the effect of liquid organic fertilizer of banana stem on the growth and productivity of 3 types of mustard. This type of research is a descriptive quantitative with an experimental method. The study design used a completely randomized design (CRD) with three treatments and eight replications. Data collection by observation using observation sheets. The data obtained were analyzed by analysis of variance (ANOVA) in one path and continued with LSD. Based on the results of the research, there are differences in the effect of giving Liquid Organic Fertilizer to banana stem on the plant height parameters of three types of mustard. The plant height parameters of chinese green cabbage, and collards meat are significantly different from those of green mustard. There are differences in the effect of giving Liquid Organic Fertilizer banana stem to the parameters of the number of leaves of three types of mustard. The parameters of the number of chinese green cabbage and green mustard leaves are significantly different from collards meat. There is a difference in the effect of Liquid Organic Fertilizer on banana stem on the wet weight parameters of three types of mustard. The parameters of wet weight of chinese green cabbage and green mustard are significantly different from collards meat.